1973
DOI: 10.1007/bf02531808
|View full text |Cite
|
Sign up to set email alerts
|

Activation of long chain fatty acids by subcellular fractions of rat liver: III. Effect of ethylenic bond position on acyl‐CoA formation ofcis‐octadecenoates

Abstract: The rates of rat liver microsomal and mitochondrial activation of the Δ4 to Δ17cis‐octadecenoate positional isomers have been investigated. The fatty acid to protein ratios required for maximum activation of the Δ8, Δ9 and Δ10 isomers were much lower than the corresponding ratios required for maximum activation of thecis‐octadecenoates with double bonds at either end of the fatty acid molecule. Also, as the incubation temperature was raised from 22–38 C the Δ8 and Δ9 isomers exhibited little change in their ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
2
1
0
Order By: Relevance
“…We were particularly interested in comparing activities of oleic (18:l[n-9]) and cis-vaccenic (18:l[n-7]) acids, since data from earlier studies in this laboratory had suggested that these naturally occurring isomers are handled differently by the ligase (Murphy and Spence, 1977). Our present finding, that the maximum reaction rate with cis-vaccenic acid exceeded that with oleate, is consistent with the observations of Lippel et al (1973). Using rat-liver microsomes, these investigators demonstrated a 50-60% difference in relative ligase activities (cisvaccenate > oleate) at high levels of fatty acid.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We were particularly interested in comparing activities of oleic (18:l[n-9]) and cis-vaccenic (18:l[n-7]) acids, since data from earlier studies in this laboratory had suggested that these naturally occurring isomers are handled differently by the ligase (Murphy and Spence, 1977). Our present finding, that the maximum reaction rate with cis-vaccenic acid exceeded that with oleate, is consistent with the observations of Lippel et al (1973). Using rat-liver microsomes, these investigators demonstrated a 50-60% difference in relative ligase activities (cisvaccenate > oleate) at high levels of fatty acid.…”
Section: Discussionsupporting
confidence: 87%
“…The reaction properties observed in this study for the brain ligase are similar to those reported for the liver enzyme in several respects. These include the sharp peak in activity around pH 8.5 (Bar-Tana et al, 1971;Pande, 1972;Lippel et al, 1973;Polokoff and Bell, 1977), an apparent K,,, of 2 mM for ATP (Polokoff and Bell, 1977), and almost total dependence on ATP as nucleotide (Bar-Tana et al, 1971;Polokoff and Bell, 1977). At 6 p~, the apparent K,,, for CoASH for the brain ligase is within the range of values reported for the liver enzyme (Groot et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of NEFAs by CoA is a prerequisite before the carnitine-dependent activities allow acyl chains to cross the mitochondrial inner membranes. Comparable acyl-CoA synthetase activities with the four isomers in the presence of responsible organelles fully support previous results obtained with cis- [38] and trans- [39] isomers under other experimental conditions. This suggests that CPT I was provided, through our experimental procedures, with equal amounts of C 18:1 -CoA isomers.…”
Section: Entry Of Fa Chains Into Mitochondriasupporting
confidence: 90%